2022
DOI: 10.1038/s41582-021-00592-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of common cerebral small vessel disease

Abstract: Cerebral small vessel disease (cSVD) is a leading cause of ischaemic and haemorrhagic stroke and a major contributor to dementia. Covert cSVD, which is detectable with brain MRI but not manifest as clinical stroke, is highly prevalent in the general population with increasing age. Advances in technologies and collaborative work have led to substantial progress in the identification of common genetic variants that are associated with cSVD-related stroke (ischaemic and haemorrhagic) and MRI-defined covert cSVD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 204 publications
0
50
0
Order By: Relevance
“…Different SVD features have been found in post-mortem brains from AD patients, such as small cortical and subcortical infarcts, microbleeds, perivascular spacing, and WMH [ 32 ]. Additionally, ApoE is the major genetic factor associated both with lobar ICH and AD [ 33 ]. The Ica1l results suggest that this protein could also be commonly regulated in AD and SVD.…”
Section: Discussionmentioning
confidence: 99%
“…Different SVD features have been found in post-mortem brains from AD patients, such as small cortical and subcortical infarcts, microbleeds, perivascular spacing, and WMH [ 32 ]. Additionally, ApoE is the major genetic factor associated both with lobar ICH and AD [ 33 ]. The Ica1l results suggest that this protein could also be commonly regulated in AD and SVD.…”
Section: Discussionmentioning
confidence: 99%
“…44 Furthermore GWAS studies in multifactorial SVS and MRI-markers of cSVD have identified associations with additional genes associated with vascular ECM function (LOX, SH3PXD2A, GPR126, VCAN, NID2, EFEMP1, HBEGF ). 40,42,43,45…”
Section: Insights Into Csvd Pathogenesis From Stroke Genetics: a Cent...mentioning
confidence: 99%
“…GWAS of MRI-markers of cSVD have for instance been more powerful than GWAS of small vessel disease related stroke (SVS, ICH), possibly in part due to larger sample sizes and the continuous nature of phenotypes such as white matter hyperintensity volume. 42,43 MRI-endophenotypes also enable to study the impact of risk variants on brain microstructure already at a very young age, 43,45 with important potential implications for our understanding of disease mechanisms across the lifespan and for devising efficient and timely preventative strategies. More broadly, combining high-resolution multimodal brain and vascular imaging, machine learning and genomics offers the potential to reveal completely novel insight into mechanisms of stroke risk, stroke outcomes and more broadly of pathways linking vascular and brain health.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary evidence points to associations with genes involved in sphingolipid metabolism, myelination, blood-brain barrier integrity, neurodevelopment, and Wnt signaling. 9…”
mentioning
confidence: 99%